THE APPLICATION OF SEMANTIC MAPPING TECHNIQUE TO ENHANCE STUDENTS’ VOCABULARY MASTERY - Yehezkiel Sinaga; Anna Stasya Prima Sari; Jontra Jusat Pangaribuan; Fiber Yun Ginting (Tomorrow's Education Journal, 2023)
This study aims to investigate the potential impact of employing the Semantic Mapping technique on improving students' proficiency in vocabulary. By examining the reactions and feedback from students who have undergone instruction using this technique, valuable insights can be gained into its efficacy in bolstering vocabulary acquisition. The findings hold significance for researchers seeking innovative approaches to enhance language learning. This research is a Classroom Action Research (CAR). The research findings showed that teaching vocabulary mastery using the Semantic Mapping Technique to the eleventh-grade students of SMA Dharma Wanita Medan could improve their vocabulary mastery. It is advisable that English teachers try applying the Semantic Mapping Technique in teaching vocabulary mastery. Quantitative data analysis shows an increase in the average score of 48% in the Pre-test, with 25% of students scoring ≥ 75. In the Formative-test, 65% of students scored ≥ 75, and 79 in the Post-test, with 80% of students achieving a value of ≥ 75. Then the results of this study increased. This research was carried out in SMA Dharma Wanita Medan with the eleventh-grade students during the academic Year 2022/2023. This research was successfully conducted at SMA Dharma Wanita Medan, as evidenced by the improved student achievement from the pre-test to the formative-test to the post-test. The results of this study are expected to provide valuable information on how to enhance students' vocabulary mastery by applying the Semantic Mapping Technique. During the research, the writer discovered that in order to improve students' vocabulary mastery skills, it is essential to create an interesting technique for students, fostering their enthusiasm for learning.